Genome sequencing in persistently unsolved white matter disorders. Issue 1 (7th January 2020) - Helman, Guy; Lajoie, Bryan R.; Crawford, Joanna; Takanohashi, Asako; Walkiewicz, Marzena; Dolzhenko, Egor; Gross, Andrew M.; Gainullin, Vladimir G.; Bent, Stephen J.; Jenkinson, Emma M.; Ferdinandusse, Sacha; Waterham, Hans R.; et al.
Abstract: Genetic white matter disorders have heterogeneous etiologies and overlapping clinical presentations. We performed a study of the diagnostic efficacy of genome sequencing in 41 unsolved cases with prior exome sequencing, resolving an additional 14 from an historical cohort ( n  = 191). Reanalysis in the context of novel disease‐associated genes and improved variant curation and annotation resolved 64% of cases. The remaining diagnoses were directly attributable to genome sequencing, including cases with small and large copy number variants (CNVs) and variants in deep intronic and technically difficult regions. Genome sequencing, in combination with other methodologies, achieved a diagnostic yield of 85% in this retrospective cohort.